LITERARY AWAKENING THE NATION’S MENTAL AND HUMAN REASON - Abdulroya Panaemalae (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
What I want to emphasize here is that in our quest to build a great civilization it is not proper for us to marginal art and literature altogether. So, please read it! Do not just watch. I would like to conclude here by quoting what Ali Shari’ati once said; “Arts is not a plaything in his hands; it is not a means for gaining pleasure, for diversion, for stupefaction, for the expenditure of accumulated energy. It is not a servant to sexuality, politics or capital.  Arts is the special trust given to man by God.”